Periodontitis in individuals with diabetes treated in the public health system of Belo Horizonte, Brazil Periodontite em indivíduos com diabetes atendidos no sistema de saúde público de Belo Horizonte, Brasil - Aline Mendes Silva; Andréa Maria Duarte Vargas; Efigênia Ferreira e Ferreira; Mauro Henrique Nogueira Guimarães de Abreu (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2010)
OBJECTIVE: The aim of the present study was to investigate the prevalence of periodontitis among individuals with diabetes who use the public health system in the city of Belo Horizonte-Minas Gerais, Brazil, and the association of this condition with socioeconomic, behavioral and clinical variables. METHODS: A cross-sectional study was carried out on a calculated sample of 300 individuals with diabetes. Periodontitis was defined as clinical attachment loss (CAL) > 3 mm in two or more non-adjacent teeth or those that exhibited CAL > 5 mm in 30.0% of teeth. All subjects were over 30 years of age and underwent a periodontal examination. Socioeconomic and behavioral characteristics as well as medical history and dental history were obtained from a structured interview. Multivariate analysis was conducted using Poisson regression. RESULTS: Among the individuals with diabetes, 6.7% exhibited good periodontal health, 68.0% exhibited gingivitis and 25.3% exhibited periodontitis. The following variables were associated with periodontitis after adjustment: male (PR 1.67 95% CI 1.12, 2.49), individuals with diabetes for more than eight years (PR 1.63 95% CI 1.63, 2.38), smokers (PR 1.71 95% CI 1.10, 2.65); individuals with more than 12 missing teeth (PR 2.67 95% CI 1.73, 4.15) CONCLUSIONS: Multiple determinants are associated with the prevalence of periodontitis among patients with diabetes. OBJETIVO: O objetivo do presente estudo foi investigar a prevalência de periodontite entre os indivíduos com diabetes que utilizam o sistema de saúde pública na cidade de Belo Horizonte, Minas Gerais, Brasil, e verificar a associação desta com condições socioeconômicas, comportamentais e variáveis clínicas. MÉTODOS: Um estudo transversal foi realizado em uma amostra de 300 indivíduos com diabetes. Todos os indivíduos tinham mais de 30 anos de idade e foram submetidos a exame periodontal. Foi considerada periodontite os quadros de perda de inserção clínica (CAL) > 3 mm em dois ou mais dentes não adjacentes ou os que apresentaram CAL > 5 mm in 30.0% dos dentes. As características socioeconômicas e comportamentais, bem como a história médica e a história odontológica foram obtidas a partir de uma entrevista estruturada. Foi realizada uma análise multivariada utilizando-se a regressão de Poisson. RESULTADOS: Entre os indivíduos com diabetes, 6,7% apresentaram boa saúde periodontal, 68,0% apresentaram gengivite e 25,3% apresentaram periodontite. As seguintes variáveis foram associadas com periodontite após o ajuste: sexo masculino (RP 1,67 95% CI 1,12, 2,49), indivíduos com diabetes há mais de oito anos (RP 1,63 95% CI 1,63, 2,38), tabagistas (RP 1,71 95% CI 1,10; 2,65), indivíduos com mais de 12 dentes (RP 2,67 95% CI 1,73, 4,15). CONCLUSÕES: Determinantes múltiplos estão associados à prevalência de periodontite em pacientes com diabetes.